Getting back on the beat: links between auditory–motor integration and precise auditory processing at fast time scales. (9th February 2016) - Tierney, Adam; Kraus, Nina
Abstract: The auditory system is unique in its ability to precisely detect the timing of perceptual events and use this information to update motor plans, a skill that is crucial for language. However, the characteristics of the auditory system that enable this temporal precision are only beginning to be understood. Previous work has shown that participants who can tap consistently to a metronome have neural responses to sound with greater phase coherence from trial to trial. We hypothesized that this relationship is driven by a link between the updating of motor output by auditory feedback and neural precision. Moreover, we hypothesized that neural phase coherence at both fast time scales (reflecting subcortical processing) and slow time scales (reflecting cortical processing) would be linked to auditory–motor timing integration. To test these hypotheses, we asked participants to synchronize to a pacing stimulus, and then changed either the tempo or the timing of the stimulus to assess whether they could rapidly adapt. Participants who could rapidly and accurately resume synchronization had neural responses to sound with greater phase coherence. However, this precise timing was limited to the time scale of 10 ms (100 Hz) or faster; neural phase coherence at slower time scales was unrelated to performance on this task. Auditory–motor adaptation therefore specifically depends upon consistent auditory processing at fast, but not slow, time scales. Abstract : We asked participants to synchronize to a pacing stimulus and then changed either the tempo or the timing of the stimulus to assess whether they could rapidly adapt. Participants who could rapidly and accurately resume synchronization had neural responses to sound with greater phase coherence at the time scale of 10 ms (100 Hz) or faster, but neural phase coherence at slower time scales was unrelated to performance on this task. Auditory‐motor adaptation, therefore, specifically depends upon consistent auditory processing at fast, but not slow, time scales.